Prophetic Leadership and Local Culture on Employee Performance Mediated by Organizational Commitment - Abdul Basir (Goodwood Publishing, 2026)
Purpose: This study aims to examine the impact of prophetic leadership and local culture on employee performance, with organizational commitment as a mediating variable, at the Central Java Provincial Culture and Tourism Office. Methodology: An associative research design was used, sampling all 88 employees via saturation sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships among variables. Results: Prophetic leadership significantly influenced both organizational commitment and employee performance. Local culture significantly affects organizational commitment but has no direct impact on performance. Organizational commitment positively impacts employee performance and mediates the relationship between prophetic leadership and performance, and between local culture and performance. Conclusions: Aligning prophetic leadership with local cultural values strengthens organizational commitment, which, in turn, enhances employee performance. Effective performance improvement requires the integration of leadership, culture, and organizational goals. Limitations: Misalignment or ineffective management of prophetic leadership and local culture may reduce employee commitment and performance, highlighting the double-edged nature of these factors when organizational expectations are unmet. Contributions: This study demonstrates that prophetic leadership, which emphasizes moral and ethical values and local culture rich in wisdom, positively contributes to employee performance. Organizational commitment reinforces these effects, acting as a bridge between leadership, culture, and performance. Novelty: This study provides insights into how leaders adopting prophetic leadership aligned with local cultural values can enhance employee performance through strong organizational commitment, offering a novel integrative perspective on leadership, culture, and performance in the public sector.